2018
DOI: 10.1055/s-0038-1649336
|View full text |Cite
|
Sign up to set email alerts
|

Global Health: Pediatric Neurology

Abstract: Neurologic disorders contribute significantly to both morbidity and mortality among children in resource-limited settings, but there are a few succinct studies summarizing the epidemiology of neurologic disorders in these settings. A review of available literature was performed to identify data on the prevalence, etiology, outcomes, and treatment of neurologic disorders in children in resource-limited settings. The burden of neurologic disorders in children is high in resource-limited settings. Barriers to opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 91 publications
0
11
0
Order By: Relevance
“…3 As increased access to antiretroviral therapy (ART) has reduced the incidence of opportunistic infections (OIs), there has been increasing concern regarding neurocognitive effects of HIV. [4][5][6][7] Multiple previous cross-sectional studies have demonstrated worse cognitive and developmental outcomes among children and adolescents living with HIV. Youth living with HIV show higher rates of neurocognitive deficits in executive function, memory, and language processing skills.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 As increased access to antiretroviral therapy (ART) has reduced the incidence of opportunistic infections (OIs), there has been increasing concern regarding neurocognitive effects of HIV. [4][5][6][7] Multiple previous cross-sectional studies have demonstrated worse cognitive and developmental outcomes among children and adolescents living with HIV. Youth living with HIV show higher rates of neurocognitive deficits in executive function, memory, and language processing skills.…”
Section: Introductionmentioning
confidence: 99%
“…3 As increased access to antiretroviral therapy (ART) has reduced the incidence of opportunistic infections (OIs), there has been increasing concern regarding neurocognitive effects of HIV. 4–7…”
Section: Introductionmentioning
confidence: 99%
“…In our study, patients with epilepsy were more likely to be children, and 85% of children under 10 who were seen at the MESH MH supported services were diagnosed with epilepsy. Globally, the burden of epilepsy is high among children [ 17 ]. In sub-Saharan Africa, it is estimated that over 90% of people with epilepsy are younger than 20 years old [ 1 ], and the prevalence of epilepsy in children is estimated to be between 3.6 and 44/1000, with higher rates in rural areas [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, the burden of epilepsy is high among children [ 17 ]. In sub-Saharan Africa, it is estimated that over 90% of people with epilepsy are younger than 20 years old [ 1 ], and the prevalence of epilepsy in children is estimated to be between 3.6 and 44/1000, with higher rates in rural areas [ 17 ]. The most common risk factors for epilepsy in resource-limited countries has been attributed to birth-related trauma, traumatic brain injuries, and central nervous system (CNS) infections, as well as inadequate access to quality health services [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation